Acute cholecystitis: early versus delayed cholecystectomy, a multicenter randomized trial (ACDC study, NCT00447304) - Gutt, Carsten N; Encke, Jens; Köninger, Jörg; Harnoss, Julian-Camill; Weigand, Kilian; Kipfmüller, Karl; Schunter, Oliver; Götze, Thorsten; Golling, Markus T; Menges, Markus; Klar, Ernst; Feilhauer, Katharina; et al. (Annals of surgery, 2013)
Acute cholecystitis is a common disease, and laparoscopic surgery is the standard of care. Optimal timing of surgery for acute cholecystitis remains controversial: either early surgery shortly after hospital admission or delayed elective surgery after a conservative treatment with antibiotics. The ACDC ("Acute Cholecystitis-early laparoscopic surgery versus antibiotic therapy and Delayed elective Cholecystectomy") study is a randomized, prospective, open-label, parallel group trial. Patients were randomly assigned to receive immediate surgery within 24 hours of hospital admission (group ILC) or initial antibiotic treatment, followed by delayed laparoscopic cholecystectomy at days 7 to 45 (group DLC). For infection, all patients were treated with moxifloxacin for at least 48 hours. Primary endpoint was occurrence of predefined relevant morbidity within 75 days. Secondary endpoints were as follows: (1) 75-day morbidity using a scoring system; (2) conversion rate; (3) change of antibiotic therapy; (4) mortality; (5) costs; and (6) length of hospital stay. Morbidity rate was significantly lower in group ILC (304 patients) than in group DLC (314 patients): 11.8% versus 34.4%. Conversion rate to open surgery and mortality did not differ significantly between groups. Mean length of hospital stay (5.4 days vs 10.0 days; P < 0.001) and total hospital costs (€2919 vs €4262; P < 0.001) were significantly lower in group ILC. In this large, randomized trial, laparoscopic cholecystectomy within 24 hours of hospital admission was shown to be superior to the conservative approach concerning morbidity and costs. Therefore, we believe that immediate laparoscopic cholecystectomy should become therapy of choice for acute cholecystitis in operable patients. (NCT00447304).